2016
DOI: 10.1017/jfm.2016.695
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Marangoni surfing

Abstract: We theoretically study the surfing motion of chemically and thermally active particles located at a flat liquid–gas interface that sits above a liquid layer of finite depth. The particles’ activity creates and maintains a surface tension gradient resulting in the auto-surfing. It is intuitively perceived that Marangoni surfers propel towards the direction with a higher surface tension. Remarkably, we find that the surfers may propel in the lower surface tension direction depending on their geometry and proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…This is appropriate for water-soluble surfactants but, for example, the opposite limit of what has been considered in Refs. [ 29 , 31 ], where surfactant is strictly confined to the interface.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…This is appropriate for water-soluble surfactants but, for example, the opposite limit of what has been considered in Refs. [ 29 , 31 ], where surfactant is strictly confined to the interface.…”
Section: Modelmentioning
confidence: 99%
“… Because for , the total Marangoni force is always positive for concentration profiles with , which are increasing toward the rear side. Vandadi et al have shown that this can change in confinement, when the high of the fluid container becomes comparable to the sphere radius [ 31 ]. For constant concentration boundary conditions (B), this means that because there is no direct Marangoni force for these boundary conditions.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Lauga & Davis (2012), Marangoni propulsion (Bush & Hu 2006;Masoud & Stone 2014) refers to 'the situation where a body, located at the surface of a fluid, generates an asymmetric distribution of surface active materials, thereby prompting a surface tension imbalance and a Marangoni flow, both of which lead to locomotion.' Examples of such bodies, which are sometimes called Marangoni surfers (Würger 2014;Vandadi et al 2017), include camphor scrapings (Van der Mensbrugghe 1870; Nakata et al 1997), organic solvent droplets (Oshima et al 2014;Janssens et al 2017), and water walking insects (Linsenmair & Jander 1963).…”
Section: Introductionmentioning
confidence: 99%